2020
DOI: 10.1186/s42834-020-00074-4
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbed leucaena protein on citrate modified Fe3O4 nanoparticles: synthesis, characterization, and its application as magnetic coagulant

Abstract: Natural coagulants from plants resources have gained a lot of attention as it is renewable, biodegradable, non-hazardous, lower cost, and less sludge generated compared to chemical coagulants. However there are still some drawbacks, namely long settling time and possible increase of dissolved organic carbon in the treated water. In this paper we tried to address these drawbacks by utilizing citrate modified Fe3O4 to adsorb protein from Leucaena leucocephala as the active coagulating agent. The effect of trisod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…24 Besides, the spectrum showed the noticeable increase of the peak at 1620 cm À1 ascribed to the C = O symmetric stretching vibration of citrate molecules, which are stabilized on the surface of the Fe 3 O 4 NPs. 20 These results revealed the presence of the -COOH groups of citrate molecules on the surface of the Fe 3 O 4 NPs. The FTIR spectrum of C-Fe 3 O 4 NPs@OVA showed peaks of the same kind observed for C-Fe 3 O 4 NPs at 580, 1403, 2920, 2853, and 3400 cm À1 demonstrating the presence of C-Fe 3 O 4 NPs (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…24 Besides, the spectrum showed the noticeable increase of the peak at 1620 cm À1 ascribed to the C = O symmetric stretching vibration of citrate molecules, which are stabilized on the surface of the Fe 3 O 4 NPs. 20 These results revealed the presence of the -COOH groups of citrate molecules on the surface of the Fe 3 O 4 NPs. The FTIR spectrum of C-Fe 3 O 4 NPs@OVA showed peaks of the same kind observed for C-Fe 3 O 4 NPs at 580, 1403, 2920, 2853, and 3400 cm À1 demonstrating the presence of C-Fe 3 O 4 NPs (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…2A(b)). 20 The XRD pattern infers the formation of the cubic inverse spinel structure of Fe 3 O 4 . 21 The XRD spectrum of C-Fe 3 O 4 NPs@OVA was recorded to understand if there were any changes in the crystalline structure of C-Fe 3 O 4 NPs in the OVA-coated C-Fe 3 O 4 NPs (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…50 The use of citrate-coated MIONPs for protein adsorption has been previously reported. 52,53 Rahman et al reported its use for bovine serum albumin (BSA) adsorption, obtaining an adsorption maximum of 83 mg g −1 at pH 4.7. 53 According to this work, the mechanism of adsorption was mostly electrostatic, due to the interaction between the negatively charged MIONPs (provided by the carboxylic groups of citrate molecules) and the positively charged BSA at low pH values.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, based on the active ingredients, natural coagulant could be classified as protein, polyphenol, and polysaccharide (Kristianto 2017). Protein from Moringa oleifera (Baptista et al 2017), Moringa stenopetala (Dalvand et al 2016), Leucaena leucocephala (Kristanda et al 2020;Kristianto et al 2020), Cocos nucifera (Fatombi et al 2013), etc. as active coagulating agent has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%